United Kingdom : Financial Sector Assessment Program-Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The U.K. financial sector is globally systemic, open, and complex. It has weathered the COVID-19 pandemic fittingly, thanks to the post-GFC reforms, a proactive macroprudential stance, and an effective multipronged response to maintain financial stability. Brexit uncertainties are being handled appropriately as the U.K. and EU authorities and the financial industry collaborate to prevent undesirable financial stability outcomes. The endpoint of the pandemic remains unclear, as does the actual impact on the financial system once support measures wane. At this juncture, therefore, financial stability conditions in the United Kingdom are being shaped by three key considerations: (i) the evolving U.K.-EU relationship on financial services; (ii) securing a sustainable and robust post-pandemic economic recovery; and (iii) successfully managing ongoing structural transitions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; United Kingdom